The effect of Plukenetia Volubilis residue on Omega-3 enriched eggs - Sittiprapaporn, Phakkharawat (Asian Journal of Medical Sciences, 2020)
Background: Omega-3 DHA-enriched eggs provide the consumer with a value-added product that delivers a clear, functional benefit for an increasingly health conscious population. Human requires an omega-6: omega-3 ratio of 4:1. The typical Thai diet which use a lot of vegetable oil for cooking provides a dramatically high 20:1 ratio. Lowering this ratio may reduce the risk of many chronic diseases including cardiovascular disease, coronary heart disease, Alzheimer's disease and some cancers. A healthy omega-6:omega-3 ratio promotes the health benefits. The increased levels of DHA provides much needed nutrient essential to human brain functions e.g. brain activities. Aims and Objective: The purpose of this study was to study the Omega-3,6,9 concentration in raw and boiled eggs feeding with Plukenetia Volubilis residue. Materials and Methods: A sample was selected from raw and boiled eggs feeding with Plukenetia Volubilis residue. Results: The result showed that total level of Omega-3 with 37869.65 mg/100mL and Omega-6 with 38490.67 mg/100mL which was not much different in Plukenetia Volubilis oil. However total Omega-9 is only 8394.74 mg/100mL compared to 37869.65 (Omega-3) and 38490.67 (Omega-6) which is almost 5 times lower than Omega-3,6.In addition, the comparison of Omega-3,6,9 concentration between raw and boiled eggs from hen feeding by Plukenetia Volubilis Oil. The total level of Omega-3,6,9 in boiled eggs was higher than in raw eggs (Omega-3: 122.85 mg/100g (raw egg), 158.12 mg/100g (boiled eggs); Omega-6: 1479.18 mg/100g (raw egg), 1766.53 mg/100g (boiled eggs); Omega-9: 3009.16 mg/100g (raw egg), 3375.23 mg/100g (boiled eggs)). Conclusion: There is constantly growing demand from consumers for food products of superior health quality. We can increase the omega-3 content of eggs through the enrichment of the layers’ diet with Plukenetia Volubilis. However, the relationship of Plukenetia Volubilis residue in chicken egg is still needed for further study.